The relevancy of mosque architecture in a multi-faith country: China as a case - Ismail, Sumarni; Liu, Yuzhou; Asif, Nayeem; Sabil, Azmal (Abdullatif Al Fozan Award for Mosque Architecture and Institut Terjemahan & Buku Malaysia Berhad, 2019)
INTRODUCTION ACCORDING to the survey by Pew Research Center for the level of religious diversity in 2010, China was defined as one of the most multi-faith countries all over the world. At present, data shows that some 20 to 40 million Muslims live in China for which the actual numbers are still difficult to obtain. They acknowledged that due to the different origins of Islam in China and the complexity of China’s modern national policy, various official and unofficial national identities1, 2. Interestingly, Chinese mosque architecture, whether historical or modern, reflects this diversity. This paper investigates the development history of mosque buildings in China3. The discussion on historical mosques continues to contemporary times, which presents diversified architectural styles for mosques in China. Especially, unlike the olden days, in the 21st century, modern architectural technology allows clients to choose from a variety of styles and materials when designing mosques to reflect specific versions of Islamic identity.